2012
DOI: 10.1128/jvi.00064-12
|View full text |Cite
|
Sign up to set email alerts
|

A Baculovirus-Encoded MicroRNA (miRNA) Suppresses Its Host miRNA Biogenesis by Regulating the Exportin-5 Cofactor Ran

Abstract: MicroRNAs have emerged as key players in the regulation of various biological processes in eukaryotes, including host-pathogen interactions. Recent studies suggest that viruses encode miRNAs to manipulate their host gene expression to ensure their effective proliferation, whereas the host limits virus infection by differentially expressing miRNAs that target essential viral genes. Here, we demonstrate that an insect virus, Bombyx mori nucleopolyhedrosis virus (BmNPV), modulates the small-RNA-mediated defense o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 55 publications
(67 reference statements)
1
84
0
Order By: Relevance
“…Recent insights into the function of baculoviral miRNAs have revealed interesting revelations about the stratagem of these viruses. Bombyx mori nucleopolyhedrovirus-encoded bmnpv-miR-1 was found to downregulate the expression of host nuclear protein Ran involved in exportin 5-mediated small RNA transport machinery (Singh et al, 2012), whilst bmnpvmiR-3 was found to be expressed during the early phase of infection and decrease the expression of baculoviral DNAbinding protein P6.9 (Singh et al, 2014). Autographa californica multiple nucleopolyhedrovirus (AcMNPV)-encoded AcMNPV-miR-1 was found to target viral gene ODV-E25, favouring the generation of occlusion-derived virions (Zhu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent insights into the function of baculoviral miRNAs have revealed interesting revelations about the stratagem of these viruses. Bombyx mori nucleopolyhedrovirus-encoded bmnpv-miR-1 was found to downregulate the expression of host nuclear protein Ran involved in exportin 5-mediated small RNA transport machinery (Singh et al, 2012), whilst bmnpvmiR-3 was found to be expressed during the early phase of infection and decrease the expression of baculoviral DNAbinding protein P6.9 (Singh et al, 2014). Autographa californica multiple nucleopolyhedrovirus (AcMNPV)-encoded AcMNPV-miR-1 was found to target viral gene ODV-E25, favouring the generation of occlusion-derived virions (Zhu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs carried by both DNA and RNA viruses can also modulate host gene expression, thereby facilitating virus infection in the animal kingdom (5,18,41). Since miRNAs and siRNAs use similar factors for their biogenesis and function, it will be of great interest to see whether viRNAs can modulate host gene expression and thereby facilitate virus infection in the animal kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Although virus-encoded miRNAs have been described in mammalian viruses, such as Epstein-Barr virus (2) and simian virus 40 (3), the miRNAs encoded by baculovirus, which infect numerous beneficial insects and agricultural pests, have only been investigated in Bombyx mori nucleopolyhedrosis virus (BmNPV) (4,5). Investigation of the miRNAs encoded by these viruses would help to explain the role of miRNAs in host-pathogen interactions.…”
mentioning
confidence: 99%